Development of a Button-Wearing Skills Programme Using Quiet Books for Mildly Mentally Disabled Children in Grade II at SLB YAPMI Rancaekek - Utami, Dewi Ayu; Pertiwi, Dwi Endah (Universitas Pahlawan Tuanku Tambusai, 2025)
Button-wearing skills are part of a self-development programme in the aspect of self-care that plays an important role in shaping the independence of children with mild intellectual disabilities. At SLB YAPMI Rancaekek, a button-wearing skills program has been developed, but in practice it has not been equipped with learning media that are appropriate to the needs of children, so that children with mild intellectual disabilities still show dependence on help from others when wearing button-wearing clothes. This study aims to determine the ability of children with mild intellectual disabilities in wearing button-wearing clothes before the development of the programme, to find out the programme currently used and the form of development of the button-wearing skills programme for children with mild intellectual disabilities in class II through the Quiet Book media at SLB YAPMI Rancaekek. The research method used is descriptive qualitative, with data collection techniques in the form of observation, interviews, documentation studies, and Focus Group Discussions (FGDs) involving teachers as the main partners in the development process. The results of the study indicate that children's ability to wear button-up clothes is still limited. After the development of the programme, children became more enthusiastic and focused when practising button-up skills gradually with the Quiet Book media. This research can make a positive contribution, particularly in developing basic skills that support the independence of children with mild intellectual disabilities in self-care, such as wearing button-down shirts in everyday life.